Swimming Training in a T2DM Zebrafish Model Restores Mitochondrial Function to Alleviate Anxiety-Like Behaviors and Metabolic Dysregulation - Fang, Yimeng; Qu, Junying; Zhao, Jing; Qu, Linkai; Wang, Lei; Luo, Cheng; Yang, Qinsi; Wu, Wei; Sun, Da; He, Dongjuan (Frontiers in bioscience (Landmark. Print), 2025)
Introduction: Anxiety and depression-like behaviors are common in patients with type 2 diabetes mellitus (T2DM). This study explored the potential of swimming training (ST) to alleviate these symptoms by restoring mitochondrial function. While aerobic exercise is known to influence mitochondrial dysfunction and behavioral abnormalities, the mechanism by which ST achieves this remains unclear. Objective: To investigate how ST improves T2DM and associated anxiety-like behaviors by regulating mitochondrial structure and function. Methods: T2DM was induced in zebrafish with a high-sugar diet, followed by 20 days of ST. Behavioral analysis assessed anxiety-like behaviors, while ELISA and microscopic imaging techniques were used to evaluate changes in mitochondrial structure and function in liver tissue. Results: ST significantly alleviated anxiety-like behavior and mitigated mitochondrial damage. Furthermore, ST counteracted mitochondrial dysfunction induced by oxidative stress through regulation of reactive oxygen species levels (p < 0.01), stabilization of mitochondrial membrane potential (p < 0.0001), and increasing the production of adenosine triphosphate (p < 0.01). ST also improved T2DM markers, including blood glucose regulation (p < 0.001), insulin level (p < 0.05), and lipid metabolism (p < 0.01 for low-density lipoprotein cholesterol (LDL-C), p < 0.01 for high-density lipoprotein cholesterol (HDL-C), p < 0.01 for total cholesterol (T-CHO)). Conclusions: This research provides insights into the intricate interplay between mitochondrial dysfunction in T2DM and behavioral outcomes while highlighting the potential of ST as a holistic therapeutic strategy for T2DM patients.